KAJIAN KRIMINOLOGIS KENAKALAN ANAK DALAM FENOMENA BALAPAN LIAR DI WILAYAH HUKUM POLRES BULELENG - Yulia, Ni Putu Rai (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2014)
Illegal race is one manifestation of juvenile delinquency, and if not dealt with quick and appropriately respons it will be a big problem. The illegal race is a “prohibited activity” and it is rule by Article 297 jo. Article 115letter b Law No. 22 of 2009 about Road Traffic and Road Transportation. In fact, in Singaraja there are many violations of these rules. Therefore, from the perspective of criminology needs to be known about the factors that cause child doing the wild race and mitigation efforts from the police. This research is a law studies with the empirical aspec, which is primary data and secondary data as a source. Processing and data analysis was done by qualitatively. Overall results of the analysis of these data are presented descriptively, and fully explained about the problem that studied and also accompanied by a critical review. Based on Containment theory proposed by Walter C. Reckless and research results, it can be seen that the factors that cause the child or juvenile do the illegal race, which is divided into 2 ( two ) that are inner and outer containment. Furthermore, It is described about the reduction of the illegal races by Buleleng Police, which is based on the results of research, there are 2 (two) reduction, that are by penal and non- penal facilities.
Keywords: Criminological; Delinquency; Illegal Race